Using Double Bubble Map Technique to Improve the Descriptive Text Writing Skill of the Tenth Graders of SMA Tarakanita Magelang in the School 2018/2019. - Rani Sulistyowati (Faculty of Education and Teachers Training, 2020)
Writing is considered as one of the difficult English skills to be mastered. The descriptive text writing skill of the tenth graders of SMA Tarakanita Magelang in the school year 2018/2019 is not satisfactory. This condition is caused by low motivation and the teacher does not use any technique in teaching descriptive.There were two main objectives in the research. The first is to know whether Double Bubble Map Technique could increase the learning motivation of the descriptive text writing skill. The second is to know how great the improvement of the descriptive text writing skill after been taught by using Double Bubble Map technique of the tenth graders of SMA Tarakanita Magelang in the school year 2018/2019 is.The writer conducted a classroom action research. It was divided into Pre-Cycle, Cycle I, and Cycle II. To collect the data, the writer used non test (observation, questionnaires, and documentation) and writing test.Based on the writer’s observation and questionnaires, it showed that most students had behavioral change. Their learning motivation increased after the writer did some treatment in Cycle I and Cycle II by using Double Bubble Map technique. There more students that paid attention and were active in learning process of descriptive text writing skill. The students got better score in descriptive writing test. It proved that students understood the writer’s explanation.